The Influence Of Problem-Based Learning Models On Critical Thinking Skills In Early Childhood - Hariyani, Desi; Haenilah, Een Yayah; ., Nopiana; Kurniawati, Asih Budi (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
The purpose of this study is to determine the effect of the problem-based learning model on the critical thinking abilities of children aged 5-6 years. This type of research uses quantitative with quasi- experimental research methods. Sampling in this study used purposive sampling with the number of samples in this study totaling 20 children and the data collection techniques used were observation and documentation. The data analysis technique used is the Wilcoxon signed rank test. This results of the research showed that the treatment scores using the problem-based learning model and the posttest were increased by 45% for children Developing According to Expectations (DAE) compared to before using the problem-based learning model. The results of the pretest for critical thinking abilities of children who were Beginning to Develop (BD) were 35%. then the final result of the total number of children's pretest and posttest is at the Very Well Developing (VWD) stage of 80%. This shows that there is an influence from using the problem-based learning model on the critical thinking abilities of children aged 5-6 years .